2022
DOI: 10.1002/hbm.25967
|View full text |Cite
|
Sign up to set email alerts
|

Predicting time‐resolved electrophysiological brain networks from structural eigenmodes

Abstract: How temporal modulations in functional interactions are shaped by the underlying anatomical connections remains an open question. Here, we analyse the role of structural eigenmodes, in the formation and dissolution of temporally evolving functional brain networks using resting‐state magnetoencephalography and diffusion magnetic resonance imaging data at the individual subject level. Our results show that even at short timescales, phase and amplitude connectivity can partly be expressed by structural eigenmodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…However, more sophisticated analysis tools exist to capture bursting events, such as the Hidden Markov modelling approach that is sensitive to distinct spectral features of bursts 31 and the "better oscillation detection" (BOSC) method, which are presumably less sensitive to noise and artefacts in the data 42 . The role for coincident bursting may be supported by studies on timeresolved functional connectivity that have demonstrated very brief periods (~0-400 ms) at which dynamic amplitude connectivity exceeds the level of stationary connectivity [43][44][45] . Importantly, a previous paper on coincident bursting using Hidden Markov Modelling indeed showed striking resemblance of coincident bursting events to power correlations 46 , though this was only analysed by assessing correlations without offering a clear mathematical and explanatory framework that explains the dissociation between coherence and power correlations.…”
Section: Discussionmentioning
confidence: 97%
“…However, more sophisticated analysis tools exist to capture bursting events, such as the Hidden Markov modelling approach that is sensitive to distinct spectral features of bursts 31 and the "better oscillation detection" (BOSC) method, which are presumably less sensitive to noise and artefacts in the data 42 . The role for coincident bursting may be supported by studies on timeresolved functional connectivity that have demonstrated very brief periods (~0-400 ms) at which dynamic amplitude connectivity exceeds the level of stationary connectivity [43][44][45] . Importantly, a previous paper on coincident bursting using Hidden Markov Modelling indeed showed striking resemblance of coincident bursting events to power correlations 46 , though this was only analysed by assessing correlations without offering a clear mathematical and explanatory framework that explains the dissociation between coherence and power correlations.…”
Section: Discussionmentioning
confidence: 97%
“…To study the connection between the structural Laplacian eigenmodes, functional connectome eigenmodes, and joint eigenmodes, we also recall the recent works in [57, 58]. The role of structural eigenmodes in the formation and dissolution of temporally evolving functional brain networks was shown in [59]. Authors in [57] investigated the association between spatially extended structural networks and functional networks using a multivariate statistical technique, partial least squares.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, eigenvectors and eigenvalues (together called eigenmodes) were extracted using diagonalization of , resulting in N eigenmodes ( N = number of ROIs). Using a recently introduced approach we mapped functional brain networks at each time point from the structural eigenmodes ( Tewarie et al, 2022 ; Tewarie et al, 2020 ). In other words, we estimated to what extent functional connectivity at each time point could be explained by a linear combination of the eigenmodes as follows: , …”
Section: Methodsmentioning
confidence: 99%